1991
DOI: 10.1128/iai.59.6.1927-1931.1991
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulation of Prevotella intermedia colonization in squirrel monkeys

Abstract: Colonization of the gingival crevice by black-pigmented Porphyromonas or Prevotella spp. (BP/P), including Porphyromonas gingivalis (formerly Bacteroides gingivalis) and Prevotella intermnedia (formerly Bacteroides intermedius), is thought to be an important ecological event which may result in the destruction of connective tissues supporting the teeth. Theoretically, periodontal diseases could be prevented if these or other periodontal pathogenic microorganisms did not colonize the subgingival area. The humor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Okuda et al (39) showed that peroral immunization with whole cells or s.c. immunization with purified P. gingivalis hemagglutinin could not eliminate the colonization of P. gingivalis in ligated hamsters. McArthur et al (32) demonstrated that immunization of squirrel monkeys with P. gingivalis or Prevotella internedia (formerly Bacteroides intermedius [7]) was associated with a significant reduction in the colonization of black-pigmented Bacteroides spp. Nisengard et al (37) reported that a heightened humoral response in monkeys to Bacteroides macacae (the monkey equivalent of the human species P. gingivalis) as a result of immunization caused a reduction in the subgingival recolonization of B. macacae.…”
Section: Discussionmentioning
confidence: 99%
“…Okuda et al (39) showed that peroral immunization with whole cells or s.c. immunization with purified P. gingivalis hemagglutinin could not eliminate the colonization of P. gingivalis in ligated hamsters. McArthur et al (32) demonstrated that immunization of squirrel monkeys with P. gingivalis or Prevotella internedia (formerly Bacteroides intermedius [7]) was associated with a significant reduction in the colonization of black-pigmented Bacteroides spp. Nisengard et al (37) reported that a heightened humoral response in monkeys to Bacteroides macacae (the monkey equivalent of the human species P. gingivalis) as a result of immunization caused a reduction in the subgingival recolonization of B. macacae.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the IgG antibodies may enhance phagocytosis and killing of oral microorganisms through activation of complement or opsonization (12,258,313,428). It has been demonstrated that systemic immunization of animals with periodontopathogens may reduce the colonization of these bacteria in the gingival crevice and reduce periodontal destruction (83,131,314,371). However, since periodontal diseases are of multifactorial origin, systemic immunization with periodontopathogens may also enhance the destruction of alveolar bone (67,122).…”
Section: Host Factorsmentioning
confidence: 99%
“…However, ferric ion destroys periodontal tissue with bacteria when periodontitis occurs. Porphyromonas gingivalis (P.g) and Prevotella intermedia (P.i) are the main pathogenic bacteria (Clark et al , ; Mysak et al , ). Pi can secret hemagglutinin and hemolysin, which can cause an increase in the iron concentration in periodontal tissue by inducing red blood cell (RBC) aggregation and rupture (Guan et al , ).…”
Section: Introductionmentioning
confidence: 99%